If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-2) + -1y = 4 Multiply 2 * -2 -4 + -1y = 4 Solving -4 + -1y = 4 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1y = 4 + 4 Combine like terms: -4 + 4 = 0 0 + -1y = 4 + 4 -1y = 4 + 4 Combine like terms: 4 + 4 = 8 -1y = 8 Divide each side by '-1'. y = -8 Simplifying y = -8
| 4t(t+5)= | | -3x+8+4x=4+x+4 | | -8z=-5-9z | | v-8=5v+8 | | -9(1+7b)=-32 | | 9-4x-6-6x=5 | | 12x-9=5x+40 | | 3x-5(x-5)=-6+5x-11 | | -7+4(7b-2)=209 | | 10-20=-b | | 2r-3.1=1.17 | | 6(2)+24=12y | | 8f=7f-10 | | r+16=30 | | -3+7(1-2x)=-94 | | 4y+11+6y+5=180 | | 4y+11+6y+5=90 | | -4h+10=-3h | | -420=910x+2310 | | N+14=3n | | -60=4(2n-7)-10n | | 7(-3x+6)=126 | | 5+-1(t+3)=-1+2(t-3) | | 6(-2)+24=-12y | | 7(-3+6)=126 | | 3a+4x=c | | 64+9f=793 | | x=2y^2-3 | | r+16=20 | | x(1/x+2)=14 | | 9-x=3x+7 | | 117-9r=36 |